2001
DOI: 10.1074/jbc.m103467200
|View full text |Cite
|
Sign up to set email alerts
|

A 49-Residue Peptide from Adhesin F1 of Streptococcus pyogenes Inhibits Fibronectin Matrix Assembly

Abstract: F1 is an adhesin of Streptococcus pyogenes which binds the N-terminal 70-kDa region of fibronectin with high affinity. The fibronectin binding region of F1 is comprised of a 43-residue upstream domain and a repeat domain comprised of five tandem 37-residue sequences. We investigated the effects of these domains on the assembly of fibronectin matrix by human dermal fibroblasts, MG63 osteosarcoma cells, or fibroblasts derived from fibronectin-null stem cells. Subequimolar or equimolar concentrations of recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
158
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(175 citation statements)
references
References 45 publications
14
158
0
Order By: Relevance
“…Although earlier reports concluded that endothelial cell signaling in 2D culture is dependent on Fn matrix assembly (Bourdoulous et al 1998), these studies employed a Fn-derived peptide as an inhibitory fragment that has since been shown to modulate cell function independently of effects on Fn fibrillogenesis (Ambesi et al 2005). Indeed, our findings, as well as those of others (Mercurius and Morla 1998;Tomasini-Johansson et al 2001), demonstrate that under 2D conditions, cell adhesion, migration, and proliferation proceed independently of Fn matrix assembly.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although earlier reports concluded that endothelial cell signaling in 2D culture is dependent on Fn matrix assembly (Bourdoulous et al 1998), these studies employed a Fn-derived peptide as an inhibitory fragment that has since been shown to modulate cell function independently of effects on Fn fibrillogenesis (Ambesi et al 2005). Indeed, our findings, as well as those of others (Mercurius and Morla 1998;Tomasini-Johansson et al 2001), demonstrate that under 2D conditions, cell adhesion, migration, and proliferation proceed independently of Fn matrix assembly.…”
Section: Discussionmentioning
confidence: 56%
“…As changes in the morphology of 3D-embedded endothelial cells correlate with Fn matrix assembly, we first sought to characterize the functional role that the fibrillogenic process plays in the tubulogenic program. To block Fn matrix assembly without affecting the initial binding of soluble Fn binding to ␣ 5 ␀ 1 , endothelial cells were incubated with (1) monoclonal antibodies directed against Fn domains embedded within, or near, the Fn III 1,2 modules that are critical for regulating Fn-Fn interactions (i.e., monoclonal antibody L8 or 9D2); (2) a 70-kDa N-terminal Fn fragment that interferes with the polymerization of intact Fn dimers by competing for matrix assembly sites on the endothelial cell surface; or (3) a 49mer peptide (termed the functional upstream domain, or FUD) derived from the Streptococcus pyogenes adhesion F1 protein, which binds directly to the N-terminal matrix assembly domain of Fn (Chernousov et al 1991;Tomasini-Johansson et al 2001, 2006Mao and Schwarzbauer 2005). As exemplified by the addition of FUD (but not the control peptide Del29, wherein FUD residue 29 is deleted), the ability of fibrin-embedded endothelial cells to assemble a Fn matrix is blocked completely in the presence of inhibitors of Fn fibrillogenesis ( Fig.…”
Section: The 3d-specific Regulation Of Endothelial Cell Function By Fmentioning
confidence: 99%
“…125 I-70K binding to cells was carried out in the absence of serum utilizing previously described methods (McKeown-Longo and Mosher, 1985;Tomasini-Johansson et al, 2001). Tissue culture plastic wells in 24-well plates were coated with laminin at 10-20ÎŒg/ml in PBS overnight at 4°C.…”
Section: Binding Of Radiolabeled 70k To Fn-/-cell Monolayersmentioning
confidence: 99%
“…To test the hypothesis that fibronectin assembly (rather than only expression, as shown in Figure 1) is required for the assembly of fibrillin-1, established function-blocking peptides for fibronectin were used (Figure 2; Tomasini-Johansson et al, 2001). Blocking formation of the fibronectin network by the peptide FUD resulted in complete inhibition of fibrillin-1 network formation, whereas the control peptide Del29 had no effect on either fibronectin or fibrillin-1 network formation (Figure 2A).…”
Section: Fibronectin Assembly Is a Prerequisite For Fibrillin Assemblymentioning
confidence: 99%
“…The established, functional upstream domain (FUD) of Streptococcus pyogenes, which efficiently inhibits fibronectin assembly (Tomasini-Johansson et al, 2001;Ensenberger et al, 2004), and its inactive mutant Del29 lacking amino acid residue I 29 (Zhou et al, 2008), were added at 500 nM to HSFs at the time of seeding (7.5 Ï« 10 4 cells/well) into eight-well chamber slides. After incubation for 48 h, the cells were processed and stained with anti-fibrillin-1 and anti-fibronectin antibodies as described in Immunofluorescence Microscopy.…”
Section: Peptide Inhibition and Protein Binding Monitored By Immunoflmentioning
confidence: 99%